Injury Risk Analysis among Judo Athletes with Intellectual Disabilities - Morales, Jose; Iteya, Misaki; Mulroy, James; Kons, Rafael; Simenko, Jozef; Fukuda, David H.; Escobar-Molina, Raquel; Guerra-Balic, Myriam; Pierantozzi, Emanuela; Moragas, Marta (International Journal of Sports Medicine, 2024)
The main aim of this study was to evaluate injury prevalence, incidence rate, and burden in judo athletes with intellectual disabilities (ID) who participate in international competitions. This retrospective cross-sectional study analyzed data from the past year for 182 judo athletes with ID. Data was collected using a self-reported questionnaire, adapted from previous research, that included questions about injuries impacting training or competition, injury type, mechanism, severity, diagnosis, and location on the body. The injury prevalence among judo athletes with ID occurred most often during training (68.2%) and primarily affected the lower extremities (35%). Age group and injury prevalence were significantly related (χ2=7.91; P=0.04), while gender, weight, and ability level were not. Results were closer to those previously reported for conventional judo, which is likely due to the lower practice intensity among judo athletes with ID. Injury prevalence was lower than in prior studies, but the incidence rates aligned when considering training time in judo athletes with ID. Injury burden analysis revealed that females had a lower burden than males, while older athletes experienced a higher burden than younger athletes. Most injuries occur during training, which is likely attributable to safety-focused competition rules.
Keywords: prevalence; incidence; injury burden; para sport; adapted judo